Mergers and Acquisitions in the German Hospital Market – Who are the Targets? - Adam Pilny (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2014)
Since the introduction of the DRG system in 2004, the German hospital market experienced a stream of consolidations in terms of mergers and acquisitions, resulting in a decreasing number of hospital owners. In this study, I examine the ex-ante characteristics of hospitals prior to a merger or an acquisition occurring between 2005 and 2010 in Germany, predominantly focusing on the financial conditions of hospitals. The results reveal that hospitals with a higher probability of default and less liquid resources are more often the targets of acquisitions. On the other hand, hospitals with a lower equity-to-assets ratio exhibit a higher probability of merger. This pattern can be explained by different motives and rationales of hospital chains and potential investors. – – Seit der Einführung des DRG-Systems im Jahr 2004 fand im deutschen Krankenhausmarkt eine Konsolidierung statt, die durch Fusionen und Akquisitionen geprägt gewesen ist. In deren Folge nahm die Anzahl der Träger im Krankenhausmarkt stetig ab. In dieser Studie werden die ex-ante Charakteristika von Krankenhäusern vor ihrer Fusion und Akquisition untersucht, wobei insbesondere der Fokus auf die finanzielle Lage der Kliniken gelegt wird. Die Ergebnisse zeigen, dass Krankenhäuser mit einer größeren Ausfallwahrscheinlichkeit und mit geringeren liquiden Mitteln häufiger von Akquisitionen betroffen sind. Dahingegen weisen Kliniken mit einer geringeren Eigenkapitalquote eine höhere Wahrscheinlichkeit auf fusioniert zu werden. Diese Ergebnisse lassen sich durch die Motive und Übernahmeabsichten seitens der Klinikketten und potenzieller Investoren erklären.
Keywords: I11; L33; 330; hospital market; mergers; acquisitions; consolidation